2022
DOI: 10.1590/1679-78257022
|View full text |Cite
|
Sign up to set email alerts
|

Predicting compressive strength of concrete with fly ash, metakaolin and silica fume by using machine learning techniques

Abstract: The compressive strength (CS) is the most important parameter in the design codes of reinforced concrete structures. The development of simple mathematical equations for the prediction of CS of concrete can have many practical advantages such as it save cost and time in experiments needed for suitable design data. Due to environmental concerns with the production of cement, different supplementary cementitious materials are often used as partial replacements for cement such as fly ash (FA), metakaolin (MK), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
1
1
0
Order By: Relevance
“…Thus, this analysis corroborates the previous observation that such additives affect compressive strength of concrete [14,21,47]. Moreover, previous studies involving compressive strength of concrete, machine learning as well as Fig.…”
Section: Influence Of Independent Variable Sensitivitysupporting
confidence: 91%
See 1 more Smart Citation
“…Thus, this analysis corroborates the previous observation that such additives affect compressive strength of concrete [14,21,47]. Moreover, previous studies involving compressive strength of concrete, machine learning as well as Fig.…”
Section: Influence Of Independent Variable Sensitivitysupporting
confidence: 91%
“…| https://doi.org/10.1007/s44290-024-00022-w Research experimental assays found the same influence of concentration and type of additives in compressive strength of concrete [16,21,23,47].…”
Section: Discussionmentioning
confidence: 91%